FORMATION OF THE EFFECTIVE INNOVATION SYSTEM AS A WAY OF IMPROVEMENT OF AGRARIAN ENTERPRISES COMPETITIVENESS - Поліщук, В. А. (Scientific Progress & Innovations, 2017)
One of the main and the most effective directions of an agrarian sector development is innovative one, as it positively effects the modernization of an agribusiness industry, improves a competitiveness on the basis of a technical and technologic renovation of production. The main components of the innovation system are business and scientific-research sectors. In the process of this system formation it is necessary to take into account peculiarities of an economic development as well as geographical and business conditions of the production. The efficiency of the innovation system is primarily associated with a number of advantages which it has: firstly, it is oriented on market needs that exclude the possibility to develop outdated innovations; secondly, the access to scientific research results will be available to not only big agrarian enterprises but small and individual agricultural producers; thirdly, that will be attracted to the work with new technologies of production, machinery, or modern organizational and economic forms, will have the opportunity to study both at educational institutions and scientific-research structures.